Enhancing two-dimensional computational approach for vortex-induced vibrations by scaling lift force. (1st December 2020) - Duranay, Aytekin; Kinaci, Omer Kemal
Abstract: Vortex-induced vibrations (VIV) are generally evaluated with relatively simpler two-dimensional (2D) methods using direct numerical simulation (DNS), large eddy simulation (LES) or RANSE-based (Reynolds-Averaged Navier-Stokes Equations) methods. Computationally, these 2D approaches have relatively lower costs which make them more suitable for such applications. However, 2D flow assumes that there are no tip-flows at both ends or no cross-flows along the moving body. Cellular shedding, which also adds three-dimensionality in VIV, is also neglected. This study proposes a simpler 2D computational approach that accounts for the three-dimensional (3D) flow for VIV. A three-dimensionality factor is introduced to the forced vibration equation which allows calibration of numerical solutions with experiments. Numerical model presented in this study is developed for practical engineering approaches and takes all three dimensional effects into account. The model is tested with two different experimental setups. The first one is with the experiments carried out at the Ata Nutku Ship Model Testing Laboratory and the second is with the experiments published in the literature. Results of this study show that as the effects of tip flow, cellular shedding and cross-flows increase, range of synchronization decreases. The other outcome of this study is that the method adopted in this paper can be used to enhance numerical simulations of vibrating bodies in fluids. Highlights: Numerical approaches to solve for VIV are generally 2D while the phenomenon itself is 3D. Three-dimensionality of VIV increases with decreasing aspect ratio. It also increases at higher Reynolds numbers. Three-dimensionality factor is introduced into the forced vibration eqn. to allow 2D assumptions to account for 3D flow. Three-dimensionality factor explicitly affects the fluid force but it also implicitly affects the phase difference.. The three-dimensionality factor allows to shrink the range of synchronization as observed in experiments.